2016
DOI: 10.1016/j.jconrel.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Microbubbles and ultrasound increase intraventricular polyplex gene transfer to the brain

Abstract: Neurons in the brain can be damaged or lost from neurodegenerative disease, stroke, or traumatic injury. Although neurogenesis occurs in mammalian adult brains, the levels of natural neurogenesis are insufficient to restore function in these cases. Gene therapy has been pursued as a promising strategy to induce differentiation of neural progenitor cells into functional neurons. Non-viral vectors are a preferred method of gene transfer due to potential safety and manufacturing benefits but suffer from lower del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Based on these reasons, extremely high amounts of nucleic acids are required when administered systemically. In regard to the issue of nucleic acids stability in vivo, it has been reported that nanoparticles of nucleic acids and polymers, such as polyethyleneimine or poly(lactic- co -glycolic acid), could increase their transfection efficiencies with ultrasound and microbubbles, via systemic injections [ 31 , 32 , 33 ]. The formation of nanoparticles with these cationic polymers reduced the risk of the degradation by nuclease and the removal from circulation.…”
Section: Bubbles For Systemic Deliverymentioning
confidence: 99%
“…Based on these reasons, extremely high amounts of nucleic acids are required when administered systemically. In regard to the issue of nucleic acids stability in vivo, it has been reported that nanoparticles of nucleic acids and polymers, such as polyethyleneimine or poly(lactic- co -glycolic acid), could increase their transfection efficiencies with ultrasound and microbubbles, via systemic injections [ 31 , 32 , 33 ]. The formation of nanoparticles with these cationic polymers reduced the risk of the degradation by nuclease and the removal from circulation.…”
Section: Bubbles For Systemic Deliverymentioning
confidence: 99%
“…These methods are used in combination with other methods, such as lipofection, to protect nucleic acid against degradation by nucleases. To increase gene delivery efficiency of sonoporation, microbubbles were shown to be effective [43] and applied for delivery to cancer cells [44,45] and the central nervous system [46,47]. Clinical trials in phases I and II have been reported for the treatment of melanoma [48][49][50] and solid tumors [51].…”
Section: Sonoporation Electroporation and Magnetofectionmentioning
confidence: 99%
“…AD) are diagnosed and treated in older patients, improved gene delivery older mice will be more relevant. Disruption of BBB to enhance delivery has been explored via microbubbles, ultrasound (Tan et al, 2016) and chemicals ( e.g. mannitol) (Kwon et al., 2010; Gray et al, 2011); but the clinical implications of such approaches are not known.…”
Section: Challenges Towards Cns-targeted Gene Deliverymentioning
confidence: 99%